2019
DOI: 10.21307/ane-2019-029
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus-seeking in rats is accompanied by increased c-Fos expression in hippocampal CA1 as well as short 22 kHz and flat 50 kHz calls

Abstract: We determined CA1 hippocampal field to be involved in self-exposure, a type of novelty-seeking behaviour that has also been associated with short 22 kHz and flat 50 kHz ultrasonic vocalizations (USV) in adult male Long-Evans rats. Rats were habituated for three days to a self-exposure cage with two nose-poke holes. On day four, the animals from the experimental group were allowed to turn the cage light off for 5 s with a nose-poke (test/self-exposure session), while rats from control-yoked group had changing l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 87 publications
(103 reference statements)
0
6
0
Order By: Relevance
“…In a recent experiment in a semi-novel environment, i.e., in a cage that had holes in the walls and was familiar to the rats but the lighting was changed so that the illumination of the cage had a novel element, rat ultrasonic vocalizations were recorded. Any time the experimental animal nose-poked the hole, the light was switched off for 5 s. The yoked control group was unable to switch the light off, but the on–off lights were controlled by the experimental group of animals [ 97 ]. It was found that rats that could control lighting performed more nose-pokes and emitted more vocalizations than the yoked rats.…”
Section: Evolution and Functions Of Rat Vocalizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent experiment in a semi-novel environment, i.e., in a cage that had holes in the walls and was familiar to the rats but the lighting was changed so that the illumination of the cage had a novel element, rat ultrasonic vocalizations were recorded. Any time the experimental animal nose-poked the hole, the light was switched off for 5 s. The yoked control group was unable to switch the light off, but the on–off lights were controlled by the experimental group of animals [ 97 ]. It was found that rats that could control lighting performed more nose-pokes and emitted more vocalizations than the yoked rats.…”
Section: Evolution and Functions Of Rat Vocalizationsmentioning
confidence: 99%
“…10–20 ms in duration) as compared to the control yoked group. Although the behavioral situation was not a typical novel environment, there was an element of novelty and novel exploration, and it was associated with calling [ 97 ]. It was concluded that 50 kHz calls and short 22 kHz calls could be associated with the investigative function and novelty seeking.…”
Section: Evolution and Functions Of Rat Vocalizationsmentioning
confidence: 99%
“…Interestingly, it was shown that rats emit 22-kHz as well as 50-kHz USV during neutral situations and not only aversive ones (Robakiewicz et al, 2019). The study by Robakiewicz et al (2019) also showed that both call types and hence presumably both emotional states can be present during an emotional neutral task of performing nose pokes in order to change the light of the experimental apparatus. Both call types were also found in a cocaine self-administration task (Barker et al, 2010), where animals received either high or low doses of cocaine.…”
Section: Discussionmentioning
confidence: 98%
“…This is also reminiscent of an approach/avoidance conflict, i.e., a situation characterized by choices leading to either reward or punishment (Aupperle et al, 2015). Interestingly, it was shown that rats emit 22-kHz as well as 50-kHz USV during neutral situations and not only aversive ones (Robakiewicz et al, 2019). The study by Robakiewicz et al (2019) also showed that both call types and hence presumably both emotional states can be present during an emotional neutral task of performing nose pokes in order to change the light of the experimental apparatus.…”
Section: Discussionmentioning
confidence: 99%
“…The other system responsible for the stress response is the autonomic nervous system (especially the sympathetic branches). In future experiments, it would be interesting to compare the neuronal structure or activities in the relevant brain areas, eg, the basolateral amygdala [35,36], perirhinal cortex [37], or hippocampus [38], etc. One weakness of this study is that the WH rats were significantly older than the SD rats.…”
Section: Plos Onementioning
confidence: 99%